The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1242/jeb.073163
|View full text |Cite
|
Sign up to set email alerts
|

How much energy should manipulative parasites leave to their hosts to ensure altered behaviours?

Abstract: SummaryAlthough host manipulation is likely to be costly for parasites, we still have a poor understanding of the energetic aspects underlying this strategy. It is traditionally assumed that physiological costs are inevitably associated with mechanisms evolved by parasites to induce the required changes in host behaviours. While most energetic expenditures of parasites relate primarily to bringing about the altered behaviours, manipulative parasites also have to consider the condition of their host during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
0
20
2
Order By: Relevance
“…This type of mechanism could explain the intensity-related effect on behavior modification identified in the current study if both host sharing and host manipulation are costly to the A. dirus parasites. Consistent with this type of hypothesis, costs of both host sharing and manipulation have been identified (e.g., Dezfuli et al 2001;Maure et al 2013). We are currently examining the potential importance of this type of mechanism in the A. dirus-C. intermedius relationship.…”
Section: Discussionmentioning
confidence: 66%
“…This type of mechanism could explain the intensity-related effect on behavior modification identified in the current study if both host sharing and host manipulation are costly to the A. dirus parasites. Consistent with this type of hypothesis, costs of both host sharing and manipulation have been identified (e.g., Dezfuli et al 2001;Maure et al 2013). We are currently examining the potential importance of this type of mechanism in the A. dirus-C. intermedius relationship.…”
Section: Discussionmentioning
confidence: 66%
“…One possible explanation for this finding is that the energy required by the host to accomplish a parasite-induced behavior such as the maintenance of aberrant surfacing behaviors represents a key energetic constraint (Maure et al, 2013). Manipulative parasites therefore have to "budget" for such costs when optimizing the exploitation of host resources as they develop Lefèvre et al, 2008;Poulin, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that host sharing can impact parasite development, growth, body size, and energy content, and that each of these factors has the potential to influence trait modification (Read and Phifer, 1959;Roberts, 2000;Dezfuli et al, 2001;Sparkes et al, 2004Sparkes et al, , 2006Benesh and Valtonen, 2007a;Franceschi et al, 2008Franceschi et al, , 2010Benesh et al, 2009a;Dianne et al, 2010Dianne et al, , 2012Caddigan et al, 2014Caddigan et al, , 2017. If competitive interactions among parasites influence the patterns of development, growth, and energy allocation, and if manipulation is costly, then parasites may benefit by adopting strategies that balance the conflicting demands associated with their own growth, and development with those that are associated with host manipulation (e.g., Poulin, 1994a;Parker et al, 2003;Thomas et al, 2005Thomas et al, , 2011Michaud et al, 2006;Ball et al, 2008;Franceschi et al, 2010;Maure et al, 2013). Consistent with this type of mechanism, infection of an aquatic isopod by an acanthocephalan parasite is associated with decreases in both parasite energy content, and modification of host behavior (mating) at higher intensities of infection (Caddigan et al, 2014(Caddigan et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%